Lembaga Pendidikan Tinggi Al-Azhar: Mengenang Peradaban Islam Masa Fatimiyah (297-567 H/909-1171 M) - Dedi Sahputra Napitupulu; Solihah Titin Sumanti (UIN Sumatera Utara Medan, 2017)
Al-Azhar is one of the institution's pride the Islamic Ummah. History has recorded how the existence of Al-Azhar of the early Fatimid Dynasty to this day holds a great story very interesting. Not only that, Al-Azhar also contribute on the development of civilization and Islamic intellectuals. Many scientists the great scientists who were born from there. One thing that is not less important is that it turns out that the existing educational system in Al-Azhar turned out at the adoption by the institutions which exist in Western countries. Therefore, this paper will try to uncover the historical return of Al-Azhar during the Fatimid Dynasty, history of the establishment, and the factors that affect the educational system.